Literature Review: Niat dan Faktor Penentu Keterlibatan dalam Sustainability Accounting pada Mahasiswa dan Akuntan Profesional - Malahusna, Nurmalia; Nugrahanti, Trinandari Prasetya (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to review and analyze the literature on factors influencing individual intentions to engage in sustainability accounting, both among students and professional accountants. Sustainability accounting has gained increasing importance in response to demands for transparency, accountability, and the integration of environmental, social, and governance (ESG) aspects into accounting practices. However, individual engagement in such practices remains shaped by a complex interplay of internal and external factors. The study employs a literature review approach by examining 10 articles published in Scopus- and Sinta-indexed journals within the period 2013–2023. Articles were purposively selected based on their relevance to the topic, publication quality, and alignment with the research objectives. The analysis classified determinants of intention into personal, social, and institutional dimensions. The findings reveal that personal factors include attitudes toward sustainability, prosocial values, and intra-personal competencies. Social factors are primarily subjective norms and perceived behavioral control, while institutional factors encompass campus support, organizational governance, and sustainability assurance practices. Students tend to be more influenced by personal attitudes and values, whereas professionals are more responsive to social norms and perceived control. Most studies have predominantly focused on intentions rather than actual behaviors, with cross-sectional designs being the most common. Furthermore, limited attention has been given to the role of regulations, digital technologies, and cross-cultural contexts. Future research is recommended to examine actual behavioral engagement in sustainability accounting by employing longitudinal or multilevel designs. Expanding cultural contexts and integrating technological dimensions would allow for a more comprehensive understanding of how intention translates into sustainable accounting practices.